Oleaginous Microalga Coccomyxa subellipsoidea as a Highly Effective Cell Factory for CO2 Fixation and High-Protein Biomass Production by Optimal Supply of Inorganic Carbon and Nitrogen - Liu, Yu; Wei, Dong; Chen, Weining (Frontiers in Bioengineering and Biotechnology, 2022)
Microalgae used for CO2 biofixation can effectively relieve CO2 emissions and produce high-value biomass to achieve “waste-to-treasure” bioconversion. However, the low CO2 fixation efficiency and the restricted application of biomass are currently bottlenecks, limiting the economic viability of CO2 biofixation by microalgae. To achieve high-efficient CO2 fixation and high-protein biomass production, the oleaginous microalga Coccomyxa subellipsoidea (C. subellipsoidea) was cultivated autotrophically through optimizing inorganic carbon and nitrogen supply. 0.42 g L-1 NaHCO3 supplemented with 2% CO2 as a hybrid carbon source performed high biomass concentration (3.89 g L-1) and productivity (324.17 mg L-1 d-1) with CO2 fixation rate (544.21 mg L-1 d-1) in shake flasks. Then used in 5-L photo-fermenter, the maximal protein content (60.93% DW) in batch 1, and the highest CO2 fixation rate (1043.95 mg L-1 d-1) with protein content (58.48% DW) in batch 2 of repeated fed-batch cultures were achieved under 2.5 g L-1 nitrate. The relative expression of key genes involved in photosynthesis, glycolysis, and protein synthesis showed significant upregulation. This study developed a promising approach for enhancing carbon allocation to protein synthesis in oleaginous microalga, facilitating the fixed carbon converse to algal protein replacing oil production in green manufacturing.